Rivals : a novel - Dailey, Janet (Boston : Little, Brown, 1989)
A mysterious inheritance reveals Flame Bennett is a distant relation of the man she is in love with. Each is the descendant of two long-feuding families and their family loyalties demand an impossible choice.
Keywords: Love stories